Sensitized Photo-oxidation of L-Dopa - Mehta, Prabha; Mehta, S.C. (Asian Journal of Chemistry, 2010)
Photo-oxidation of L-Dopa was carried out by singlet molecular oxygen. Eosin yellow, rose bengal and methylene blue were used as dye sensitizers. After completion of reaction the products were isolated and characterised as carbon dioxide and dopamine by m.p., elemental analysis and spectral methods. The photo-oxidation was also carried out in the presence of singlet oxygen scavenger.